2012
DOI: 10.1016/j.ccr.2012.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Acquired Docetaxel Resistance in Prostate Cancer through Depletion of Notch- and Hedgehog-Dependent Tumor-Initiating Cells

Abstract: Summary Acquired resistance to Docetaxel precedes fatality in hormone-refractory prostate cancer (HRPC). However, strategies that target Docetaxel resistant cells remain elusive. Using in vitro and in vivo models, we identified a subpopulation of cells that survive Docetaxel exposure. This subpopulation lacks differentiation markers and HLA class I (HLAI) antigens, while overexpressing the Notch and Hedgehog signaling pathways. These cells were found in prostate cancer tissues and were related to tumor aggress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
356
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 375 publications
(382 citation statements)
references
References 37 publications
16
356
1
1
Order By: Relevance
“…Previous work by our group and others correlated the activation of NF-kB/interleukin (IL)-6 pathways with docetaxel resistance in CRPC models and in patients (11)(12)(13). Other studies support a role of JUN/AP-1, SNAI1, and NOTCH2/Hedgehog signaling pathways in the development of resistance to docetaxel or paclitaxel (14,15). Moreover, it has been shown that the inhibition of androgen receptor (AR) nuclear translocation and AR activity may be an important mechanism of taxane action in prostate cancer (9).…”
Section: Introductionmentioning
confidence: 90%
“…Previous work by our group and others correlated the activation of NF-kB/interleukin (IL)-6 pathways with docetaxel resistance in CRPC models and in patients (11)(12)(13). Other studies support a role of JUN/AP-1, SNAI1, and NOTCH2/Hedgehog signaling pathways in the development of resistance to docetaxel or paclitaxel (14,15). Moreover, it has been shown that the inhibition of androgen receptor (AR) nuclear translocation and AR activity may be an important mechanism of taxane action in prostate cancer (9).…”
Section: Introductionmentioning
confidence: 90%
“…48 Moreover, suppression of acquired docetaxel resistance in prostate cancer is through depletion of Notch-dependent tumor-initiating cells. 49 GSI inhibitor suppressed Notch pathway and enhanced the antitumor effect of docetaxel in prostate cancer. 50 Recently, one study validated that activation of Notch-1 synergized with multiple pathways in promoting castration resistant prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…8 Another recent study found a small subset of CK18 − /CK19 − cells in docetaxel-resistant cell lines (Du145-DR and 22Rv1-DR) and primary as well as metastatic PCa patient samples that express low levels of differentiation marker (HLA). 11 Using a lentiviral reporter system, this group has shown that CK18 − /CK19 − cells in both Du145-DR and 22Rv1-DR models can survive docetaxel exposure and acquire chemoresistance via upregulation of Notch and Hedgehog signaling, whereas targeting these two pathways can abolish the chemoresistance both in vitro and in vivo. 11 Of note, a small subset of HLA − cells from both xenografts and primary patient samples are much more tumorigenic than the bulk HLA + cells, 11 suggesting that HLA − PCa cells may be enriched in PCSCs that are chemoresistant.…”
Section: Normal Prostate Stem/progenitor Cellsmentioning
confidence: 99%